Preliminary evaluation of WRF physical parameterizations for a frost event in Southern Brazil - Machado, Jeferson [UNESP]; Quadro, Mário; Cardoso, Camila; Araújo, Carlos; Rodrigues, Gabriel; Costa, Natália; Rodrigues, Tuanny; de Paula, Lourenço (My University, 2018)
Based on numerical simulations performed with the WRF model for a frost event in Southern Brazil in July 2013, it was possible to test different physical parameterizations and evaluate these parameterizations in these weather conditions. Although the results do not show considerable statistical differences, the experiment utilizing the Dudhia for shortwave radiation, RRTM for longwave radiation schemes, WSM6 for microphysics and YSU for boundary layer showed better results in the frost event, as it had the lowest values of ME and RMSE for the minimum temperature, relative humidity and wind speed. However, it was not possible to determine which parametrization produce the largest impact from these experiments. A greater number of frost events must be simulated with WRF model in order to obtain a more robust statistical analysis.

A partir de simulaciones numéricas realizadas con el modelo WRF para un evento de helada en el sur de Brasil, en julio de 2013, es posible evaluar diferentes parametrizaciones físicas y determinar las que más se adaptan en estas condiciones meteorológicas. Aunque los resultados no demuestran grandes diferencias estadísticas, el conjunto de parametrizaciones que utiliza los esquemas Dudhia de onda corta, RRTM de onda larga, WSM6 para microfísica y el esquema YSU para capa límite planetaria, fue el más ajustado en un evento de helada, ya que presenta los valores más bajos de ME y RMSE para la temperatura mínima, humedad relativa y velocidad del viento. Sin embargo, no se puede determinar qué parametrización influye más a partir de estos resultados. Es importante destacar que las parametrizaciones aún deben probarse con más eventos de helada simuladas por el modelo WRF, con la finalidad de obtener un análisis estadístico más robusto.
Evaluación preliminar de las parametrizaciones físicas del modelo WRF para un caso de helada en el sur de Brasil
Keywords: Frost; Helada; Modelo WRF; Parametrizaciones físicas; Physical Parameterizations; WRF Model